PRIMARY FACTORS OF PROFESSIONAL COMPETENCE FORMATION IN TEACHERS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the situation in the education system today, the ideas from the concept of the development of the public education system of the Republic of Uzbekistan until 2030, the Cabinet of Ministers of the Republic of Uzbekistan "Improving the procedure for attestation of pedagogic personnel of preschool, general secondary, secondary special, professional and extracurricular educational organizations "Measures" contains opinions and comments about the aspects of the tasks defined for the teaching profession, as well as a number of forms of education.